1993
DOI: 10.1002/pola.1993.080311014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thermal properties of poly(cycloalkyl methacrylate)s bearing bridged‐ and fused‐ring structures

Abstract: Radical polymerizations of some cycloalkyl methacrylates bearing bridged‐ and fused‐ring structures, i.e., bornyl methacrylate (BoMA), isobornyl methacrylate (IBoMA), 2‐decahydronaphthyl methacrylate (DNMA), and 3‐tetracyclo [4.4.02,5.17,10] dodecyl methacrylate (TCDMA), were carried out. The radical polymerization reactivities of these monomers depended on the structure of the cycloalkyl ester groups in the following order: TCDMA > BoMA > DNMA > CHMA > IBoMA > MMA, where CHMA and MMA are cyclohexyl and methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 19 publications
5
49
1
Order By: Relevance
“…Various poly(meth)acrylates bearing bulky ester groups, such as bornyl, 1 isobornyl, 1-3 adamantyl [4][5][6][7] and its derivatives, [4][5][6][8][9][10][11] have been synthesized to improve the thermal properties, such as the glass transition temperature and the thermal degradation temperature, of poly(methyl methacrylate) (PMMA). For example, the incorporation of adamantyl groups into polymer structures generally produces not only a high thermal stability but also an improvement in other physical and chemical properties, such as transparency to ultraviolet light, low dielectric constant, hydrophobicity, high oxidation resistance, low surface energy and high density.…”
Section: Introductionmentioning
confidence: 99%
“…Various poly(meth)acrylates bearing bulky ester groups, such as bornyl, 1 isobornyl, 1-3 adamantyl [4][5][6][7] and its derivatives, [4][5][6][8][9][10][11] have been synthesized to improve the thermal properties, such as the glass transition temperature and the thermal degradation temperature, of poly(methyl methacrylate) (PMMA). For example, the incorporation of adamantyl groups into polymer structures generally produces not only a high thermal stability but also an improvement in other physical and chemical properties, such as transparency to ultraviolet light, low dielectric constant, hydrophobicity, high oxidation resistance, low surface energy and high density.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, it has been revealed that k 1 decreases with an increase in bulkiness of the substituent. Consequently, those monomers with smaller k 1 values polymerize rapidly to high molecular weight.…”
Section: Polymerizationmentioning
confidence: 99%
“…A significant decrease in k 1 of methacrylic ester by introduction of a bulky and rigid cycloalkyl ester group has been reported, 12 and a bulky ester substituent of tX-ethylacrylates was expected to decrease the termination rate. If the tX-ethylacrylate bearing the bulky ester alkyl group has similar kP and smaller k 1 values than those of MEA, the tX-ethylacrylate could polymerize to high molecular weight as a result of a favorable balance between the slow propagation and termination rates.…”
mentioning
confidence: 98%
“…The most striking feature of the polymer properties is the strong increase in glass transition temperature (T A) as a function of IBMA concentration. [8] The IBMA homopolymer has a T 8 above 200°C. Polymers with appreciable levels of IRMA have T 6's above ISO°C.…”
Section: Introductionmentioning
confidence: 99%